Genetic Variants Associated with Lp(a) Lipoprotein Level and Coronary Disease - Clarke, Robert; Peden, John F; Hopewell, Jemma C; Kyriakou, Theodosios; Goel, Anuj; Heath, Simon C; Parish, Sarah; Barlera, Simona; Franzosi, Maria Grazia; Rust, Stephan; Bennett, Derrick; Silveira, Angela; et al. (The New England journal of medicine, 2009)
Using a novel gene chip, investigators identified single-nucleotide polymorphisms (SNPs) from three chromosomal regions, including the LPA locus, that were associated with the risk of coronary disease. Two SNPs in LPA were strongly associated with both the level of Lp(a) lipoprotein and the risk of coronary disease. After adjustment for the Lp(a) lipoprotein level, the association with the risk of coronary disease was abolished. These findings support a causal role of an increased Lp(a) lipoprotein level in the risk of coronary disease. Two SNPs in the LPA locus were strongly associated with both the level of Lp(a) lipoprotein and the risk of coronary disease. These findings support a causal role of an increased Lp(a) lipoprotein level in the risk of coronary disease. Genomewide association studies have identified several novel susceptibility loci for coronary artery disease, 1 – 4 but it is likely that only common variants can be detected in this way. 5 , 6 Moreover, loci that are identified with the use of genomewide association studies explain only a small amount of the expected contribution to the risk of coronary disease. The use of arrays of high-density single-nucleotide polymorphisms (SNPs) in candidate genes for cardiovascular disease may help elucidate the genetic contribution to the risk of coronary disease. A recent genomewide association study showed that a cluster of genes — solute carrier family 22 member . . .